2010
DOI: 10.1159/000303053
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligodeoxynucleotide Against Tissue Factor Inhibits Human Umbilical Vein Endothelial Cells Injury Induced by Anoxia-Reoxygenation

Abstract: Aims: The role of antisense oligodeoxynucleotide against tissue factor (aODN/TF) in cultured human umbilical vein endothelial cells (HUVECs) subjected to anoxia-reoxygenation (A/R) was investigated. Methods: HUVECs were divided randomly into control group, A/R group, aODN/TF+A/R group, sense oligodeoxynucleotide (sODN/TF) + A/R group and mismatched oligodeoxynucleotide (mODN/TF) + A/R group, in the latter 3 groups, HUVECs were transfected with aODN/TF, sODN/TF and mODN/TF respectively. HUVECs in all A/R groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…On the molecular biology front, miR-19 [61], short hairpin RNA [62], hairpin ribozyme [63], or antisense ODN [64–66] readily downregulates TF mRNA translation and expression.…”
Section: Regulation Of Tissue Factor Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the molecular biology front, miR-19 [61], short hairpin RNA [62], hairpin ribozyme [63], or antisense ODN [64–66] readily downregulates TF mRNA translation and expression.…”
Section: Regulation Of Tissue Factor Expressionmentioning
confidence: 99%
“…Metformin, an antidiabetic agent, suppresses the production of TNF α [59], a known factor for insulin resistance [213215]. Antisense oligonucleotide blocking TF expression prevents leukocyte adhesion following renal ischemic reperfusion injury [66, 270]. COX inhibitors readily show anti-inflammation [152, 153] as well as antithrombosis.…”
Section: Antagonisms Against Tf Signaling-evolving Thrombotic or mentioning
confidence: 99%
“…Interestingly, treating rats with TF‐ASO successfully reduced ischemia–reperfusion‐induced liver injury (Nakamura et al ., ). Similarly, in vitro treatment of human umbilical endothelial cells with TF‐ASO diminished injury induced by anoxia–reoxygenation (Yin et al ., ). We developed a hepatotoxicity model in mice by administration of a sub‐toxic p.o.…”
Section: Introductionmentioning
confidence: 97%
“…10 To examine PMN-EC interactions, an in vitro PMN-EC adhesion model was established. 43 In this model, EC injured by A/R express various inflammatory mediators such as adhesion molecules, interleukins, growth factors, cytokines and chemokines, 44 facilitating PMN-EC adherence. We found that treatment of PMN with HB-EGF significantly decreased PMN-EC adherence 4 h after A/R, and this effect was reversed with EGFR inhibition.…”
Section: Discussionmentioning
confidence: 99%